Zinner's syndrome: A rare diagnosis of congenital seminal vesicle cyst and renal agenesis on basis of radiological imaging and its management. (August 2022) - Regmi, Aavishkar Raj; Mishra, Sarmendra; Gurung, Adarsh; Acharya, Archana; Paneru, Laxman Dutta; Ghimire, Ajnish
Abstract: Introduction and importance: Seminal vesical cyst (SVC) together with ipsilateral renal agenesis known as Zinner's syndrome is a rare congenital malformation mostly asymptomatic and is detected in second to fourth decade of life presenting with symptoms of bowel and bladder neck irritation/obstruction. Diagnosis is based mainly on various imaging techniques with MRI being the confirmatory. Recent management includes laparoscopic excision of the SVC but conventional aspiration of the cystic fluid together with explorative open excision of the cyst is still regarded useful. Case presentation: A 32 years old male presented with urgency and frequency of micturition, constipation, post ejaculatory pain and USG, CT, MRI findings suggestive of right renal agenesis and bilateral seminal vesicle cyst. Clinical discussion: As other studies show, our patient is a sexually active male with characteristic symptoms of bladder and bowel obstruction. USG, CT, MRI were used for diagnosis co-relating other studies. Intervention was done by aspiration of the cystic fluid and open surgical excision of the cyst. Conclusion: Zinner's Syndrome is uncommon cause of symptoms of bowel and bladder obstruction in young men; whose diagnosis is mostly based on imaging techniques. Highlights: Seminal vesical cyst (SVC) together with ipsilateral renal agenesis known as Zinner's syndrome is rare. It is detected in second to fourth decade of life presenting with symptoms of bowel and bladder neck irritation/obstruction. Diagnosis is based mainly on various imaging techniques with MRI being the confirmatory. Conventional aspiration of the cystic fluid together with explorative excision of the cyst is still regarded useful.